#### Answer

$x = 4$

#### Work Step by Step

$6 = x + 2$
In order to solve this algebraic expression, we need to join the constants together on the left hand side. We do not move the coefficient of the variable since we have only one unknown. To calculate this, we subtract 2 from both sides of the equation in order to eliminate the constants from the right hand side as shown:
$6 - 2 = x + 2 - 2$
Simplify to get:
$4 = x$
Rearranging it, we have:
$x = 4$
This means that the expression has a possible solution at $x = 4$
If we need to test the answer, we replace for x with 4 in the original equation as below:
$6 = x + 2$
$6 = 4 + 2$
Simplify to get:
$6 = 6$
6 is equal to 6. This shows that the solution $x = 4$ is also correct.